The specificity of the place and its connotations in the novel "The Andalusian house" Loasini al aaraj : semiotics approach - Hallaci , Warda (Social Empowerment Journal, 2021)
This study aims to find the significance and specificity of the place in the novel "The Andalusian House", as a stand-alone victory in itself, because most of the studies that dealt with the place in the novel merely referred to it as a framework, or in the context of its talk of time, or narrative space. Thus, like other elements of the novel, he did not receive critical and research attention despite the complex problems he poses, relating to the past, present and future of the Algerian man, this is what we have seen in the novel "The Andalusian House", which represents a rich museum of various spatial aspects.